Empowering students through video-based teaching: unleashing the advantages of engaging educational content / Nurul Amira Azmi, Nurfaznim Shuib and Phaveena Primsuwan - Azmi, Nurul Amira; Shuib, Nurfaznim; Primsuwan, Phaveena (Universiti Teknologi MARA, Kedah, 2023)
This article critically examines the limitations of conventional teaching methods, including issues of student disengagement and limited knowledge retention. In light of these challenges, there is a growing recognition of the need to explore innovative approaches that can significantly enhance learning outcomes. The primary aim of this study is to showcase the transformative potential of video-based teaching as a solution to these pedagogical concerns. Particularly, we introduce a novel dimension to video-based teaching by incorporating interactive pop quizzes through the utilization of Padlet, which fosters active student engagement and offers immediate feedback. Furthermore, this article investigates the broader societal benefits that video-based teaching can provide. By democratizing education, this approach effectively increases accessibility and bridges the learning divide among diverse student populations. Additionally, researchers scrutinize the commercial potential associated with video-based teaching, shedding light on the prospects for educational technology development and growth within the market. The study also highlights the pivotal role of video-based teaching in enhancing teacherstudent dynamics. By fostering stronger relationships and enabling personalized instruction, this methodology creates an optimal learning environment. Consequently, it empowers learners to cultivate self-directed and continuous educational journeys, effectively preparing them to meet the evolving demands of the future. Moreover, the integration of multimedia elements within video-based teaching serves as a catalyst for multidimensional learning experiences. By catering to diverse learning styles and stimulating cognitive processes, this approach effectively enriches the educational encounter. In conclusion, this study underscores the substantial potential of video-based teaching to revolutionize education by addressing various pedagogical challenges, bridging knowledge gaps, and unlocking avenues for commercial growth. By embracing this innovative approach, educators, policymakers, and entrepreneurs can play a significant role in transforming the educational landscape, resulting in improved student engagement, enhanced learning outcomes, and a thriving market for educational technology.